Intervención neuropsicológica para estimular las funciones cognitivas de atención, memoria y percepción en adultos mayores del centro diurno de atención al adulto mayor Saraguro, 2022-2023 - Lozano González, Inti Pacuri (2023)
The present research of curricular work had as general objective: to implement the neuropsychological intervention to stimulate the cognitive functions of attention, memory and perception in older adults with mild and moderate cognitive status of the day care center for the elderly Saraguro. A quantitative, descriptive and cross-sectional approach with a quasi-experimental design was considered. The sample consisted of 10 older adults, 5 corresponding to the experimental group and 5 belonging to the control group, the brief Neuropsi test and the Mini mental exam were applied. The results found in the groups, in the levels of attention, memory and perception indicates that the majority are located at normal level is followed by moderate level and a low percentage at severe level; in relation to cognitive status of the older adults in the experimental group and control group are in a mild and moderate cognitive state; Regarding the execution of the neuropsychological program in the basic, medium and high levels reach 100% of the participants of the experimental group, develop on the activities of cognitive stimulation reaching a level of achievement; as for the verification of the efficacy by means of the U test of Mann Whitney, by means of the short post-test Neuropsi of the experimental group and control resulting in 0. 014 and in the Mini Mental 0.015 since the two values are lower than the average level of 0.05 which, the same general hypothesis is accepted that indicates older adults with mild and moderate cognitive status who participate in neuropsychological intervention to stimulate the cognitive functions of attention, memory and perception present a good performance of these functions, than older adults in the control group. Concluding that the neuropsychological program did have significance in stimulating the cognitive functions of older adults in the experimental group unlike the control group. Keywords: Cognitive status, cognitive stimulation, cognitive impairment, neuropsychological intervention.